Направления развития технологий и оборудования для экстракции пищевых ингредиентов при обогащении продуктов питания и создании функциональных продуктов - Vasilyev A. S., Shegelman I. R., Vapirov V. V. (Innovative technologis in science and education, 2017)
on the basis of the detailed patent search, the directions of the development of technologies and equipment for the extraction of food ingredients for the enrichment of food products and the creation of functional products are examined.
Keywords: патент; patent; обогащение продуктов питания; создание функциональных продуктов; экстракция пищевых ингредиентов; 105/5000 obogashcheniye produktov pitaniya; sozdaniye funktsional'nykh produktov; ekstraktsiya pishchevykh ingrediyentov; enrichment of food products; creation of functional products; extraction of food ingredients